The Behaviorist Learning Theory from an Islamic Psychopedagogical Perspective and Its Implications for Modern Learning - Ardi, Hafidz; Batubara , Juliana; Deliani , Nurfarida (The Future of Education Journal, 2025)
This article explores the behavioristic learning theory from psychological, pedagogical, and Islamic perspectives. The study aims to analyze the fundamental concepts of behaviorism, including stimulus-response mechanisms, reinforcement, and habit formation, and to identify their relevance in contemporary education. Using a qualitative descriptive approach, this article synthesizes the views of major behaviorist theorists such as Pavlov, Skinner, and Thorndike, along with Islamic perspectives on human potential and learning ethics. The findings show that behaviorism remains relevant in modern education, especially in structured learning, skill habituation, adaptive technology, and behavioral therapy. However, this theory needs to be integrated with cognitive, constructive, and spiritual dimensions to form a holistic learning framework-especially within Islamic education that emphasizes moral development and internal awareness.